Epilepsy surgery, visual fields, and driving: a study of the visual field criteria for driving in patients after temporal lobe epilepsy surgery with a comparison of Goldmann and Esterman perimetry. Issue 1 (1st January 2000) - Manji, H; Plant, G T
Abstract : Twenty four patients who had undergone temporal lobe surgery for epilepsy were assessed to determine ( a ) whether or not they had developed a visual field defect and ( b ) if a field defect was present, were the visual field criteria, as required by the DVLA, fulfilled using the monocular Goldmann perimeter test and the automated binocular Esterman method performed on a Humphrey perimeter. A field deficit was found in 13 of 24 (54%) using the Goldmann perimeter and 11 of 24 (46%) by the Esterman method. The second was a more lenient assessment with six of 24 (25%) failing the driving criteria compared with 10 of 24 (42%) by the monocular Goldmann method. Three patients were seizure free but failed the driving criteria. This complication of surgery for temporal lobe epilepsy needs to be discussed with patients before surgery.